ISOLATION AND CHARACTERIZATION OF BACTERIAL COMMUNITY IN ROOT OF CHILI PLANT AS POTENTIAL PLANT GROWTH-PROMOTING BACTERIA - Nur 'Azamiyah Ab Rani; Aslizah Mohd Aris (Journal of Academia, 2022)
Agricultural sectors contributed as a significant sector to the growth of the Malaysian economy. Thus, the sustainability of agriculture sectors played a role to maintain the success of this sector. Unfortunately, dependency on the application of synthetic chemical fertilizers and pesticides is required special attention due to its negative effect for prolong usage by this sector. Attention to the search for alternative strategies is urgently needed. Thus, the plant growth-promoting bacteria (PGPB) showed great potential as biofertilizers and biocontrol of pathogens. This research attempt aims to isolate and identify the potential PGPB from the local chilli plant’s roots. Isolation and characterization of the potential isolates of PGPB were performed using standard microbiology procedures to isolate the PGPB. A total of 10 isolates were successfully obtained during the isolation stage. The isolates were designated as strain A1 to strain A10. Based on Gram staining, strain A1, A2, A5, A6, A7, A8, A9 and A10 were found to be Gram-positive. Strain A2, A3, and A4 were found to be Gram-negative. However, strain A7 was not able to be retrieved after a series of restreaking procedures, perhaps due to symbiosis factors. Besides, strain A5 and A10 were found to be unmatched to any PGPB strain. The further biochemical analysis proposed strain A1, A3, A6, and A8 belong to Bacillus sp., strain A2 and A4 belong to Pseudomonas sp., and strain A9 proposes to be Brevibacillus sp.. In conclusion, it is strongly suggested that these nine isolates belonged to PGPB due to the strain identification, resembling a common PGPB strain. In future, a study on the ability of the isolates as bioprotectant and biofertilizers is recommended.